Hubungan antara indeks massa tubuh dan lingkar pinggang dengan nyeri kepala dan kualitas tidur - Lisbeth Meilina; Hasan Sjahrir; Khairul P Surbakti; Aida Fithrie (Fakultas Kedokteran USU, 2014)
Background and Purpose : Body mass index and waist circumference are the simple anthropometric measurement which can be used to assess nutritional state. Body mass index and waist circumference has been related with several conditions including headache and quality of sleep. The aim of this study was to assess the association between body mass index and waist circumference with headache and quality of sleepMethods : This cross sectional study had subjects which divided into two groups : headache group from Cephalgia Clinic of Neurology Department Haji Adam Malik Hospital and non headache group by matching age and gender from General Clinic of Neurology Department Haji Adam Malik Hospital. Every subject experienced the measurement of body weight, height to assess body mass index and measurement of waist circumference. A questionnaire about headache adapted from study HO K-H & Ong BK-C was given to subject from headache group. Pittsburgh Sleep Quality Index was given to subject from headache group and non headache group.Result : From 108 subjects consist of 54 subjects from headache group and 54 subjects from non headache group, there were 10 men (18.5%) and 44 women (81.5%) in each group. From 54 subjects of headache group there were 22 subjects (40,7%) with migren and 32 subjects (59.3%) with tension type headache. There were 16 subjects had good sleep quality and 38 subjects had poor sleep quality in headacahe group. There were 28 subjects had good sleep quality and 26 subjects had poor sleep quality in non headache group. There was no significant association between body mass index (p= 1.000) and waist circumference (p= 0.241) with headache. There was a significant association between body mass index (p= 0.041) and waist circumference (p= 0.023) with quality of sleep.Conclusion : There was no significant association between body mass index and waist circumference with headache. There was a significant association between body mass index and waist circumference with quality of sleepKey words : body mass index; waist circumference; headache; quality of sleep.